SURVEI MINAT SISWA DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMP NEGERI 1 GANDUSARI KABUPATEN TRENGGALEK - Abdillah Nuruddin; Eko Hariyanto (Jayabama: Jurnal Peminat Olahraga, 2024)
Physical education learning is a medium for developing individuals as a whole physically, mentally, physically and socially.. Interest influences the academic process and academic achievement. Interest cannot be separated from needs and desires, which need to be cultivated by educators or instructors. The research aims to determine students' interests when taking part in physical education at Public Junior High School 1 Gandusari, Trenggalek Regency. This is quantitative descriptive research with a survey method. The population in this study was 647 students Junior High School 1 Gandusari students, Trenggalek Regency and A total of 100 students were sampled in this research. This research instrument has been tested by experts. Techniques for analyzing data using percentages with the assistance of Microsoft Excel software, which is then described in a frequency table and histogram. The results of this research show that students' interest in participating in learning physical education at Public Junior High School 1 Gandusari, Trenggalek Regency is very high, namely 85% and the high category is 15%.